2022
DOI: 10.1093/toxsci/kfac003
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage and Repair and Epigenetic Modification in the Role of Oxoguanine Glycosylase 1 in Brain Development

Abstract: Oxoguanine glycosylase 1 (OGG1) repairs the predominant reactive oxygen species (ROS)-initiated DNA lesion 8-oxoguanine (8-oxoG). Human OGG1 polymorphisms resulting in reduced DNA repair associate with an increased risk for disorders like cancer and diabetes, but the role of OGG1 in brain development is unclear. Herein, we show that Ogg1 knockout mice at 2-3 months of age exhibit enhanced gene- and sex-dependent DNA damage (strand breaks) and decreased epigenetic DNA methylation marks (5-methylcytosine, 5-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Previous studies of ROS-mediated developmental disorders have consistently shown that models deficient in proteins involved in DNA damage recognition and repair signaling [ 37 , 38 ], DNA repair [ 13 , 15 , 30 , 39 ] or antioxidative activity [ 22 , 35 ] were more susceptible to developmental disorders caused by several different ROS-initiating teratogens, and in some cases even caused by physiological levels of ROS formation in untreated animals [ 14 , 30 , [34] , [35] , [36] , 40 , 41 ]. This study's findings align with these previous observations, as Brca1 direct KO +/- embryos exhibit enhanced γH2AX following both saline and EtOH exposures, with the latter showing an additive effect.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of ROS-mediated developmental disorders have consistently shown that models deficient in proteins involved in DNA damage recognition and repair signaling [ 37 , 38 ], DNA repair [ 13 , 15 , 30 , 39 ] or antioxidative activity [ 22 , 35 ] were more susceptible to developmental disorders caused by several different ROS-initiating teratogens, and in some cases even caused by physiological levels of ROS formation in untreated animals [ 14 , 30 , [34] , [35] , [36] , 40 , 41 ]. This study's findings align with these previous observations, as Brca1 direct KO +/- embryos exhibit enhanced γH2AX following both saline and EtOH exposures, with the latter showing an additive effect.…”
Section: Resultsmentioning
confidence: 99%
“…ESR1 inhibition is important in the formation of long-term memory in the mouse hippocampus [ 48 ], and a role for OGG1 in repressing ESR1 to modulate learning and memory formation has been postulated because hippocampal regions of Ogg1 KO mice exhibited upregulation of Esr1 target genes [ 17 ]. We previously saw OGG1- and sex-dependent enhanced DNA strand breaks, decreased DNA methylation levels and behaviour deficits including alterations in spatial and recognition memory in untreated OGG1-deficient young mice (~2–3 months) [ 10 ]. The presence of sex-dependent differences in young OGG1-deficient mice suggests that estrogen may play an important role in regulating gene expression in an OGG1-dependent manner, particularly during development, so Esr1 and Esr2 mRNA levels and protein levels were quantified in fetal brains.…”
Section: Discussionmentioning
confidence: 99%
“…However a decreased performance in an open field box test (measured via number of crossed lines, number of rears, mean speed and time immobile) was observed in aging (26 months) Ogg1 − / − mice (sexes combined and tested at 20 lux) [ 50 ]. Our own data using 3-month-old untreated OGG1-deficient mice showed no differences in open field activity except for a trend for increased time spent in the centre zone by Ogg1 −/− females when tested at ~50 lux [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of Ogg1 in the brain leads to various cellular and molecular events, including increased apoptosis and abnormal neuronal connectivity (Wong et al, 2008 ), key pathomorphological features of autism. In fact, Bhatia et al ( 2022 ) explored the involvement of OGG1, using OGG1 knockout mice, in brain development and its role in repairing DNA lesions induced by reactive oxygen species. Their findings demonstrate that young Ogg1 knockout mice displayed sex- and gene-specific DNA damage, reduced DNA methylation marks, elevated cerebellar calbindin levels, impaired hippocampal function, altered body weight and various behavioral abnormalities, highlighting the significance of OGG1 in normal brain development through its potential functions in DNA repair and epigenetic regulation, with implications for NDDs.…”
Section: Mixed Modelsmentioning
confidence: 99%